2018
DOI: 10.1016/j.jacbts.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

l-Phenylalanine Restores Vascular Function in Spontaneously Hypertensive Rats Through Activation of the GCH1-GFRP Complex

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Although there was no significant difference in arginine and NO synthase activity between low salt and high salt diets, the NO levels were significantly decreased in hypertensive SS rats [ 33 ], which was due to decreased BH 4 in the kidney and reduced NO production in the vasculature by uncoupling NOS. Confirming previous findings, we found that L-Phe supplementation reversed the inhibitory GCH1-BH 4 complex in both the vasculature and kidneys, thus likely contributing to the increased NO production and decreased blood pressure [ 22 , 23 ]. Furthermore, BH 4 , as an allosteric and essential cofactor for NO synthase, plays a critical role in the stabilization of the NO synthase dimer and increases the affinity of NO synthase for arginine [ 22 , 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although there was no significant difference in arginine and NO synthase activity between low salt and high salt diets, the NO levels were significantly decreased in hypertensive SS rats [ 33 ], which was due to decreased BH 4 in the kidney and reduced NO production in the vasculature by uncoupling NOS. Confirming previous findings, we found that L-Phe supplementation reversed the inhibitory GCH1-BH 4 complex in both the vasculature and kidneys, thus likely contributing to the increased NO production and decreased blood pressure [ 22 , 23 ]. Furthermore, BH 4 , as an allosteric and essential cofactor for NO synthase, plays a critical role in the stabilization of the NO synthase dimer and increases the affinity of NO synthase for arginine [ 22 , 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…For assessment of L-phenylalanine supplementation, all 7-week-old male SS rats were maintained on low salt diets and had free access to water. The L-Phe supplementation group was given free access to drinking water with 2.5% w/v L-Phe and low salt diets as described previously [ 23 ]. After 4 days of stable baseline blood pressure, the low salt diets were switched to a high salt diet for another 14 days (n = 7–9).…”
Section: Methodsmentioning
confidence: 99%
“…52 (3) Phenylalanine can be involved in NO production, reducing superoxide species and enhancing vascular function. 53 (4) Histidine is the precursor of histamine which is synthesized by the action of the histidine decarboxylase enzyme inside mast cells and basophils. 54 As histamine is released in T1 when the patient is recovered at T2, histidine would decrease since it could be used to replenish histamine in the mast cells granules.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that during anaphylaxis, mast cells, basophils and neutrophils induce hypotension, vascular hyper‐permeability and an endothelial production of nitric oxide (NO) 52 . (3) Phenylalanine can be involved in NO production, reducing superoxide species and enhancing vascular function 53 . (4) Histidine is the precursor of histamine which is synthesized by the action of the histidine decarboxylase enzyme inside mast cells and basophils 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations revealed that majority of the predominantly downregulated metabolites in OCC and OPC patients postchemoradiation were nitric oxide‐related precursor, modulator, and/or catalyst such as aspartic acid, phenylalanine, L‐ornithine, L‐proline, xanthine, tyrosine, and glycine 48‐52 . These findings indicate that metabolites presence in saliva reflects the microbiome communities and support the postulation of the loss of nitric oxide bioavailability in OCC and OPC patients postchemoradiation, due to the reduced abundance of oral nitrate‐reducing bacteria.…”
Section: Discussionmentioning
confidence: 59%